Late post partum hemorrhage - causes and defining aspects: Case series in Zainoel Abidin General Hospital, Banda Aceh, Indonesia - Bram Pradipta; Cut Meurah Yeni (Proceedings of The Annual International Conference, Syiah Kuala University - Life Sciences & Engineering Chapter, 2011)
Improving skill and knowledge in making a diagnosis and management of late post partum hemorrhage.Globally, more than half a million women die annually due to pregnancy and childbirth. Bleeding causes 28% of the direct causes of maternal deaths and remains the most common cause of maternal death. In developing countries, several countries have maternal mortality ratio over 1000 women per 100,000 live births, and WHO statistics illustrates that 25% of maternal deaths resulting from post partum hemorrhage, which counted more than 100,000 maternal deaths per year. Postpartum hemorrhage can be divided into 2 types: early postpartum hemorrhage, which occurs within 24 hours of delivery, and late postpartum hemorrhage, which occurs 24 hours to 6 weeks after delivery. Most cases of postpartum hemorrhage, greater than 99%, are early postpartum hemorrhage. Notably, most women are still under the care of their delivering provider during this time. But a few are considered late postpartum hemorrhage. Here we presented case series consisted of two cases with late postpartum hemorrhage. Both of them enrolled in Zainoel Abidin General Hospital OBGYN emergency ward as an outpatient post c-section patient. The first case was a 38 years old Indonesian women, Parity 4, post-cesarean section that comes with hypovolemic shock and post partum hemorrhage and foul smelling lochia. Six days after treatment the patient is discharged with good condition with abnormalities found in the form of disturbances of uterine contractions and uterine infection. The second case was a 19 years old, parity 1, post-Caesarean section 120 days ago for CPD indication that comes with recurrent bleeding after the operation. Curettage of the endometrium was then done to the patient in Bireun Hospital prior to the Zainoel Abidin General Hospital, but the bleeding persisted. Patients were then treated for 10 days and discharged with good condition with a diagnosis of abnormal uterine bleeding. With many women delivering outside of hospitals and early postpartum hospital discharge being a growing trend, postpartum hemorrhage that presents to the emergency department may be either early or late. Late post partum hemorrhage though a minority still poses great risk to maternal health. Key management of both early and late HPP are rapid assesment and diagnosis of conditions, restoration of blood volume and simultaneously search for the cause. HPP diagnosis is confirmed by observing the amount of bleeding and the patient's clinical symptoms. Management of HPP requires teamwork and a systematic yet comprehensive management